The influence of temperature and solvent quantity on soxhlet extraction process towards total phenolic content (TPC) - Setyowati, Diyosi Dwi (Social Agriculture, Food System, and Environmental Sustainability, 2024)
Banana is a giant herbaceous plant with elongated large leaves from the Musaceae family. Several types of bananas (Musa acuminate, M. balbisiana, and M. paradisiaca) produce edible fruits that are named the same. Banana production in Indonesia is quite large. According to the Fixed Figures (ATAP) in 2013, banana production reached 6.28 million tons. The purpose of this research is to determine the total phenol content in kepok banana peels using the extraction method (soxhlet) with variations of solvents, namely ethanol and methanol. First, the material is cleaned, dried under the sun and oven, then blended into powder, made into simplisia, then extracted in a soxhlet tube, and the final step is separation. The results of the analysis obtained stated that the highest phenol content was obtained in methanol solvent, namely 0.82 mg/g GAE.